Mis- or Missed Diagnosis: A Series of Four Cases - Sheela Sreedharan; Bhat Sangeetha Govinda; Iyer Satishkumar Krishnan; Kumar Kavita Krishna (Case Reports in Dentistry)
Diagnosis forms the backbone of treatment planning. Accurate diagnosis is essential to initiate the appropriate treatment at the apt time. Diagnosis involves eliciting the signs and symptoms of the patient and their accurate interpretations. The subtle signs that can go unnoticed lead to misdiagnosis and subsequent agony to the patient. Alertness on part of the clinician is important to avoid this error. Reported in this paper are four cases that were wrongly diagnosed either due to lack of clinical experience or due to omission of careful clinical, radiographic, and histopathological examinations.